"Don't be so gay!": queers, bullying, and making schools safe - Short, Donn (Law and society series, 2013)
Drawing on interviews with queer youth and their allies in the Toronto area, the author considers the effectiveness of safe school legislation and concludes that the current legislation is often more responsive than proactive., "Recent cases of teen suicide linked with homophobic bullying have thrust the issue of school safety into the national spotlight. In 'Don't Be So Gay!' Queers, Bullying, and Making Schools Safe, Donn Short considers the effectiveness of safe-school legislation. Drawing on interviews with queer youth and their allies in the Toronto area, Short concludes that current legislation is more responsive than proactive. Moreover, cultural influences and peer pressure may be more powerful than legislation in shaping the school environment. Exploring how students' own experiences, ideas, and definitions of safety might be translated into policy reform, this book offers a fresh perspective on a hotly debated issue." -- Publisher's description.